Concept map as an integrative teaching-service tool in permanent health education: report of experience (Research, Society and Development, 2020)
Objective: To present the experience of building and using the conceptual map (CM) to support permanent health education in the teaching-service integration, through the perception of professionals involved in the process. Method: Experience report lived by master's students during the Health Education Module II, of the Professional Master's in Family Health (MPSF) at the State University of Ceará (UECE). The study took place in the municipality of Maracanaú, Ceará, in the period from October to November 2015, in four stages: 1. Contact and scheduling with professionals representing Management, Social Control, the Teaching-Service Integration Commission, the Higher Education and the Integrated Health Residence Preceptorship of the State of Ceará School of Public Health; 2. Conversation wheel guided by three self-reflective questions for the construction of the MC using the CmapTools program; 3. Presentation of the MC to the class of the discipline and 4. Revisitation and validation of the MC with health professionals. Results and Discussions: The MC proved to be a facilitator of learning through the relationship of concepts and the creation of connections with other concepts. There was little use by professionals due to the lack of knowledge and embarrassment in the interrelation of concepts, but they understand that it is a resource that allows an expanded view of the process, based on the different concepts that are interconnected. Final Considerations: The use of the CM enabled the development of cognitive skills, through significant strategies of permanent education, facilitating the mediation of the challenges and contributing to the reframing of practices and processes in the teaching-health service relationship.